Anticyclonic Eddies Connecting the Western Boundaries of Indian and Atlantic Oceans. Issue 11 (5th November 2018) - Laxenaire, R.; Speich, S.; Blanke, B.; Chaigneau, A.; Pegliasco, C.; Stegner, A.
Abstract: The Indo‐Atlantic interocean exchanges achieved by Agulhas Rings are tightly linked to global ocean circulation and climate. Yet they are still poorly understood because they are difficult to identify and follow. We propose here an original assessment on Agulhas Rings, achieved by TOEddies, a new eddy identification and tracking algorithm that we applied over 24 years of satellite altimetry. Its main novelty lies in the detection of eddy splitting and merging events. These are particularly abundant and significantly impact the concept of a trajectory associated with a single eddy, which becomes less obvious than previously admitted. To overcome this complication, we have defined a network of segments that group together in relatively complex trajectories. Such a network provides an original assessment of the routes and the history of Agulhas Rings. It links 730, 481 eddies into 6, 363 segments that cluster into Agulhas Ring trajectories of different orders. Such an order depends on the affiliation of the eddies and segments, in a similar way as a tree of life. Among them, we have identified 122 order 0 trajectories that can be considered as the major trajectories associated to a single eddy, albeit it has undergone itself splitting and merging events. Despite the disappearance of many eddies in the altimeter signal in the Cape Basin, a significant fraction can be followed from the Indian Ocean to the South Brazil Current with, on average, 3.5 years to cross the entire South Atlantic. Plain Language Summary: Mesoscale eddies are ubiquitous structures in the ocean and are one of the major sources of ocean variability. They play a crucial role in physically shaping the ocean general circulation, in transporting and mixing energy, chemicals, and other materials within and among ocean basins. This should be true, in particular, south of Africa where the largest mesoscale eddies, the so‐called Agulhas Rings, are shed from the Agulhas Current into the Cape Basin conveying Indian warm and salty waters into the Southeast Atlantic Ocean. However, due to their small‐scale and highly variable nature, ocean eddies are inadequately sampled and poorly reproduced in numerical models. Hence, we still lack a good assessment of their population and an appropriate understanding of their dynamics and exact role in the Earth's climate. We propose here an original assessment on Agulhas Rings achieved by a tracking algorithm that we applied over 24 years of satellite altimetry. Its main novelty lies in the detection of eddy separation and coalescence events that replace the concept of trajectories by the consideration of an eddy network. Such a network provides an original assessment of the routes and history of Agulhas Rings longer and more complex than previously described. Key Points: New eddy tracking method including eddy merging and splitting improves assessments from satellite‐mapped fields Agulhas Rings show very complex behavior with much longer lifespan and geographical reach than previously thought They play a major role in efficiently connecting western boundary currents of the South Indian and Atlantic Oceans